Epidemiologia molecular das estirpes LaSota e São João do Meriti do vírus da Doença de Newcastle - Fernandes, Camila Cesario [UNESP] (2014)
Newcastle disease virus (NDV) is the agent that causes one of the most important diseases in birds and represents a threat to industrial aviculture. NDV is a member of the Paramyxoviridae family, Paramyxovirinae subfamily, Avulavirus genus. Viruses consist of single-stranded, non-segmented, negative-sense, RNA, associated with diseases in respiratory tract, digestive and nervous in birds. The ND control is based on biosafety, use of vaccines and early detection of infected batches. Here we present the complete genome sequence and phylogenetic analysis of a lentogenic strain (LaSota) and a velogenic strain (APMV-1/Chicken/Brazil/SJM/75) of NDV. The results revealed that the genome of LaSota and APMV-1/Chicken/Brazil/SJM/75 are constituted respectively by a total of 15,186 and 15,192 nucleotides and six genes in the order 3'-NP-P-M-F-HN-L-5’. The cleavage site of fusion protein (F) in LaSota strain shows the amino acid sequence found in non-virulent NDV strains, as opposed to happen with APMV-1/Chicken/Brazil/SJM/75 strain, the cleavage site of the F protein has the amino acid sequence corresponding to that found in virulent strains of NDV. The complete genome of LaSota strain showed no genomic differences and the phylogenetic analysis evidenced that this strain is classified in genotype II. The APMV-1/Chicken/Brazil/SJM/75 strain there are large differences in the genomic sequences and in the deduced amino acid sequences of its major structural proteins, so the phylogenetic analysis of the complete genome was demonstrated that this virus is classified in genotype V. This study can contribute significantly to understand better the genomic evolution of NDV in Brazil and in Americas, such as these strains with genotypic and phenotypic characteristics were no longer isolated in Brazil after 1975, while continued to be isolated in North America